SAP geopolymer sprayed concrete and application thereof in primary lining of high-ground-temperature tunnel

By using SAP ground polymer spray concrete in high ground temperature tunnel construction, the problem of sprayed concrete evaporation too fast, early strength increases but long-term strength decreases, and prone to deformation and cracking in high ground temperature environments is solved, and good thermal insulation is achieved and support function.

CN119390398APending Publication Date: 2025-02-07HENAN POLYTECHNIC UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411672355.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In high ground temperature environment, sprayed concrete faces problems such as excessive moisture evaporation, early strength increases, long-term strength decreases, and prone to deformation and cracking in tunnel construction. At the same time, the high thermal conductivity of ordinary concrete cannot achieve good support and heat insulation functions at the same time.

Method used

SAP is made of polymer spray concrete, which consists of gelling material, alkali trigger, river sand, gravel, water and highly absorbent resin (SAP). SAP forms a microporous structure in the concrete, reducing thermal conductivity and improving toughness.

Benefits of technology

SAP ground polymer spray concrete reduces the thermal conductivity of concrete in high ground temperature environments, improves its thermal insulation capacity, reduces construction costs and operation and maintenance costs, and meets the strength requirements of the initial lining of the tunnel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390398A_ABST
    Figure CN119390398A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of tunnel construction, and discloses SAP geopolymer sprayed concrete and application thereof in primary lining of a high-ground-temperature tunnel. The concrete is prepared from the following raw materials in parts by mass: 100 parts of a cementing material, 13-16 parts of an alkali activator, 135-150 parts of river sand, 165-185 parts of stones, 32-41 parts of water and a proper amount of SAP, in percentage by mass, the use amount of the SAP is 0.2-0.3% of the binding material; the cementing material is composed of slag and fly ash according to a mass ratio of (0.24-0.26): 1. The SAP geopolymer sprayed concrete is applied to primary lining of a high-ground-temperature tunnel. The SAP geopolymer shotcrete not only has high strength and high toughness of traditional shotcrete, but also has good heat insulation and heat resistance, has supporting and heat insulation performance, realizes environment-friendly and pollution-free construction, and is particularly suitable for high-ground-temperature tunnels and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tunnel construction, and in particular relates to SAP geopolymer shotcrete and application thereof in primary lining of a high geothermal tunnel. Background Art

[0002] High ground temperature is becoming an increasingly prominent engineering problem that seriously affects safe construction and the stress of supporting structures. It is predicted that there will be 10 tunnels with high ground temperature (air temperature exceeds 28°C during construction) along the planned railway line of the middle section of the Sichuan-Tibet Railway - Ya'an to Linzhi, with the highest ground temperature reaching 89.0°C; the ground temperature of 50~89.9°C appeared during the construction of the Sangzhuling Tunnel of the Sichuan-Tibet Railway, which has been completed. In addition, many railway and highway construction projects are located in the Himalayan geothermal zone, forming a large number of high-geothermal tunnels.

[0003] At present, the construction of high geothermal tunnels mainly adopts temporary or external measures such as strengthening and improving ventilation, spraying low-temperature water, ice cooling and mechanical refrigeration to improve the heat damage problem. The above measures have reduced the ambient temperature to a certain extent, but the construction cost has increased significantly. The high geothermal problem in tunnel construction has become increasingly prominent, and inorganic insulation lining structure has become an important measure for the prevention and control of heat damage. Sprayed concrete is widely used in tunnel construction projects, mining projects, etc. As an important support structure, it provides a fast and efficient construction method to cope with complex geological conditions. However, due to the high geothermal environment, the water in the sprayed concrete evaporates too quickly, and it is difficult for the water on the surface layer to enter the interior of the concrete, making it difficult to carry out later maintenance. In addition, the high geothermal environment will increase the early strength of the concrete, but the long-term strength will shrink, and under the action of thermal-mechanical coupling, it is easy to deform and crack, and even lose its support function. Moreover, ordinary concrete has a high thermal conductivity of 1.5~2.0W / (m·K), and it cannot achieve good support and thermal insulation functions at the same time when used as an initial support material.

[0004] In order to achieve the construction goal of high-standard, high-quality, safe and reliable tunnel projects in high geothermal environments, the research and development of new shotcrete with both support and heat-resistant and heat-insulating functions urgently needs to be broken through. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a SAP geopolymer shotcrete and its application in primary lining in high geothermal tunnels.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A SAP geopolymer shotcrete is prepared from the following raw materials in the following mass proportions, measured by mass: 100 parts of cementitious material, 13-16 parts of alkali activator, 135-150 parts of river sand, 165-185 parts of gravel, 32-41 parts of water and a proper amount of SAP (super absorbent resin); in terms of mass percentage, the amount of SAP is 0.2-0.3% of the cementitious material; the cementitious material is composed of slag and fly ash in a mass ratio of (0.24-0.26):1.

[0007] Preferably, the slag is S95 grade slag.

[0008] Preferably, the fly ash is Class I fly ash.

[0009] Preferably, the particle size of the SAP is 300-500 μm.

[0010] Preferably, the alkaline activator is compounded from water glass and NaOH, and the modulus of the alkaline activator is 1.1-1.3.

[0011] Preferably, the modulus of the river sand is 2.5-2.9.

[0012] Preferably, the stone is a natural stone with a continuous grade of 5 to 12 mm.

[0013] Preferably, based on the total mass of the stones, the composition of the 5-12 mm continuously graded natural stones is: 35-45% of 5-8 mm small-size stones, 35-45% of 8-10 mm medium-size stones, and 10-30% of 10-12 mm large-size stones.

[0014] Preferably, the preparation process is: (1) Preparation of alkaline activator: Calculate and weigh the required water glass and NaOH according to the modulus of water glass and the modulus of the alkaline activator. Pour the weighed NaOH into the water glass and stir immediately. After stirring, seal the mixture and place it at room temperature for 6 to 8 hours before use. (2) Weigh various raw materials in proportion. First, place river sand and gravel in a concrete mixer and dry mix them. Then pour slag, fly ash and SAP into the concrete mixer and dry mix them. Then pour the alkali activator into the concrete mixer and stir until the material becomes gelled. Then pour in a portion of water and stir evenly. Then pour in the remaining water and stir evenly again to obtain SAP geopolymer shotcrete.

[0015] The SAP geopolymer shotcrete is used in the primary lining of a high ground temperature tunnel.

[0016] In the present invention, super absorbent polymer (SAP) is a new functional polymer material, which has the ability to absorb hundreds or even thousands of times its own weight of water and can keep the water from flowing out. SAP can absorb a large amount of water in the early stage of mixing concrete, and slowly release the water when the internal environment of the concrete tends to be dry, thereby alleviating the drying phenomenon inside the concrete and promoting the hydration reaction of the cementitious material; SAP forms closed micropores in the hardened concrete, and the micropores can not only reduce the risk of brittle cracking of the shotcrete and improve its toughness, but also a large number of closed micropore structures exist in the concrete system, which can greatly reduce the thermal conductivity of the concrete and improve the thermal insulation capacity of the shotcrete; geopolymer is a silicon-oxygen tetrahedron [SiO4] prepared by activating industrial waste and minerals rich in silicon and aluminum (fly ash, slag, coal gangue, kaolin, etc.) with an alkali activator 4- and aluminum oxide tetrahedron [AlO4] 5- It is a unit three-dimensional network-like inorganic polymer gelling material, which can be directly produced at room temperature, which can not only reduce CO2 emissions by 80%, but also save energy consumption in the production process, and is more environmentally friendly. Geopolymer is a stable oxide network structure system, so it not only has strong acid corrosion resistance and thermal stability, but also has excellent properties of high strength, early strength, heat insulation and heat resistance.

[0017] Beneficial effects: (1) Concrete cracking has always been a key problem that plagues tunnel lining structure construction. The application of SAP super absorbent resin can play an internal nourishing role in the hydration and hardening stage, reducing the plastic cracking of concrete during the concrete hardening process; (2) SAP super absorbent resin forms closed micropores in hardened concrete, which can reduce the risk of brittle cracking of shotcrete, improve its toughness, and reduce construction and operation and maintenance costs; (3) The large number of closed microporous structures in the concrete system can significantly reduce the thermal conductivity of concrete, improve the thermal insulation capacity of shotcrete, reduce the ambient temperature of the tunnel, and reduce the use of other cooling measures, thereby significantly reducing the project cost; (4) Due to the addition of SAP, the compressive strength of SAP geopolymer shotcrete is reduced, but the reduction is not large, only about 10%, which can fully meet the strength requirements of the primary lining of the tunnel. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : Schematic diagram of the tunnel model.

[0019] Figure 2 : Schematic diagram of the tunnel surrounding rock temperature field under 80℃ high ground temperature environment.

[0020] Figure 3 : Temperature distribution of surrounding rock after tunnel excavation under different high geothermal environments.

[0021] Figure 4 : Schematic diagram of tunnel clearance temperature monitoring line (red line).

[0022] Figure 5 :Temperature changes of tunnel clearance monitoring line under 40℃ high ground temperature environment.

[0023] Figure 6 : Temperature changes of tunnel clearance monitoring line under 60℃ high ground temperature environment.

[0024] Figure 7 :Temperature changes of tunnel clearance monitoring line under 80℃ high ground temperature environment. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the described embodiments, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0026] Example 1

[0027] A shotcrete is made of the following raw materials in the following mass proportions, measured by mass: 100 parts of cementitious material, 15 parts of alkali activator, 144 parts of river sand, 176 parts of gravel, 36 parts of water and an appropriate amount of SAP (super absorbent resin); in terms of mass percentage, the amount of SAP is 0%, 0.2% and 0.3% of the cementitious material respectively; the cementitious material is composed of slag and fly ash in a mass ratio of 1:4, that is, 20 parts of slag and 80 parts of fly ash; wherein the slag The slag is S95 grade slag; the fly ash is Class I fly ash; the average particle size of the SAP is 400 μm; the alkali activator is compounded from water glass and NaOH, and the modulus of the alkali activator is 1.2; the modulus of the river sand is 2.71; the gravel is 5-12 mm continuously graded natural gravel, and its composition, based on the total mass of the gravel, is: 40% of 5-8 mm small-size gravel, 40% of 8-10 mm medium-size gravel, and 20% of 10-12 mm large-size gravel.

[0028] The preparation process is: (1) Preparation of alkaline activator: The alkaline activator is compounded from water glass and NaOH. According to the following calculation formula, the required water glass and NaOH are calculated and weighed according to the initial modulus of the water glass and the modulus of the alkaline activator. The weighed NaOH is poured into the water glass and stirred immediately. After stirring, the mixture is sealed and placed at room temperature for 8 hours before use. ; Where: G is the mass of NaOH to be added to the water glass; G1 is the mass of the water glass; N is the percentage of SiO2 in the water glass; M1 is the initial modulus of the water glass; M2 is the modulus of the alkaline activator; P is the purity of NaOH; 40 is the molecular weight of NaOH; 60 is the molecular weight of SiO2; (2) Weigh various raw materials in proportion. First, place river sand and gravel in a concrete mixer and dry mix for 60 seconds. Then pour slag, fly ash and SAP into the concrete mixer and dry mix for 60 seconds. Then pour the alkali activator into the concrete mixer and stir until the material becomes gelled. Then pour a portion of water and stir evenly. Then pour the remaining water and stir evenly again. Pour the evenly mixed mixture into a three-row mold of 100mm×100mm×100mm (length×width×height of a single-row inner cavity). Cover with plastic wrap and place in a curing box at the corresponding curing temperature (20℃, 40℃, 60℃ and 80℃) and relative humidity of 95% for curing. After curing for 24 hours, demould the sample. After demoulding, continue to place the sample at the corresponding curing temperature and cure to the corresponding age for mechanical properties tests of compressive strength and tensile strength as well as thermal conductivity tests.

[0029] (3) Test results (3.1) The test results of thermal conductivity are shown in Table 1. Generally speaking, the higher the porosity, the lower the thermal conductivity, because the thermal conductivity of air (the main filler in the pores) is much lower than that of solid materials. However, if the porosity is too high, more interconnected pores may be formed, which may increase the thermal conductivity because the convective heat transfer and radiation heat transfer of the gas may increase. It can be found from Table 1 that under the condition of 20℃~60℃, the thermal conductivity gradually increases with the increase of curing temperature. This is attributed to the fact that the curing temperature increases the density of the concrete specimen and reduces the porosity inside the concrete. Under the condition of 80℃, the water in the pores inside the concrete will evaporate rapidly. On the one hand, it cannot fully react. On the other hand, due to the high temperature and too fast reaction, the microstructure of the generated cementitious product is uneven and the density is relatively low. In addition, the high curing temperature makes it easy to produce more microcracks inside the concrete, and the porosity increases, thereby reducing the thermal conductivity. Moreover, compared with the thermal conductivity of ordinary concrete of 1.5~2.0W / (m·K) (Deng Shiling. Study on Thermodynamic Properties of Lightweight Aggregate Concrete and Lining Insulation Optimization of High Rock Temperature Tunnels [D]. Chongqing Jiaotong University, 2023.) or the blank group (no admixture), the thermal conductivity of geopolymer concrete decreases significantly after adding SAP, indicating that the concrete in the present invention has good thermal insulation and heat resistance. The reduction of lining thermal conductivity has a significant impact on high geothermal tunnels. First, reducing the thermal conductivity of the lining can more effectively control the temperature in the tunnel, reduce the temperature rise caused by heat transfer, thereby reducing the dependence on ventilation and cooling systems and reducing energy consumption. At the same time, reducing the thermal conductivity can also improve the working environment of the tunnel, improve the comfort and work efficiency of the operators, and avoid health risks caused by high temperatures.

[0030]

[0031] (3.2) The 28-day compressive strength test results are shown in Table 2. It can be found from Table 2 that: at 20°C and 40°C, the 28-day compressive strength of the geopolymer concrete mixed with SAP is improved compared with the blank group, but at 60°C and 80°C, it is reduced compared with the blank group, but the reduction is not large, which can fully meet the strength requirements of the tunnel lining; the above results show that the concrete strength of the present invention is relatively high.

[0032]

[0033] (3.3) The 28-day tensile strength test results are shown in Table 3. It can be found from Table 3 that: at 20°C and 40°C, the 28-day tensile strength of geopolymer concrete after adding 0.2% and 0.3% SAP is improved compared with the blank group; at 60°C and 80°C, the 28-day tensile strength of geopolymer concrete after adding 0.2% SAP is increased compared with the blank group, while the 28-day tensile strength of geopolymer concrete after adding 0.3% SAP is reduced compared with the blank group, but the reduction is not large, which can fully meet the toughness requirements of tunnel lining; the above results show that the concrete of the present invention has good toughness.

[0034]

[0035] In order to verify the application effect of the SAP geopolymer shotcrete prepared by the present invention in the primary lining of a high geothermal tunnel, a simulation test was carried out using finite element numerical software Comsol.

[0036] According to relevant technical specifications, when the face air temperature is lower than 28°C, the temperature effect is not considered in tunnel construction; when the face temperature is higher than 28°C, corresponding cooling measures are taken according to the temperature. 28°C is a dividing temperature.

[0037] The model size is set to 80m*100m (model width*model height), the tunnel excavation radius is 5.0m, and the lining thickness is 0.5m. The tunnel model schematic is as follows Figure 1 As shown in the figure, the black area in the middle is the tunnel excavation area, and the mesh area around the tunnel is the surrounding rock area. The simulation related parameters are derived from the software database and are reliable. The model related parameters are shown in Table 4.

[0038]

[0039] The simulation assumes three high ground temperature conditions: 40℃, 60℃ and 80℃, and the initial lining temperature is 20℃.

[0040] Figure 2 It shows the schematic diagram of the surrounding rock temperature field distribution when the initial temperature of the high geothermal environment is 80℃ and the tunnel temperature is 20℃. The surrounding rock temperature field gradually expands outward along the circular section of the tunnel, presenting a "temperature adjustment circle" as a whole. The closer the surrounding rock area is to the tunnel section, the greater the heat flux exchange and the greater the temperature change gradient.

[0041] Under different high ground temperatures, the distribution shape of the surrounding rock temperature field is similar. However, the higher the initial temperature, the greater the gradient of the surrounding rock temperature change at the same location, and the more intense the heat exchange. A surrounding rock temperature monitoring line is extended from the tunnel boundary. The measurement line position is as follows: Figure 2The red line shows the middle. Different initial high ground temperatures (40℃, 60℃, 80℃) were used for excavation simulation to obtain the surrounding rock temperature distribution after tunnel excavation under different high ground temperature environments, as shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the closer the surrounding rock is to the tunnel boundary, the more drastic the temperature change; as the distance from the tunnel boundary increases, that is, the deeper it develops into the surrounding rock, the more the temperature gradually becomes stable. Therefore, when constructing a high-temperature tunnel, corresponding thermal insulation measures should be taken to reduce drastic temperature changes and ensure construction safety to a certain extent.

[0042] Taking 28°C as the demarcation temperature, the initial temperature of the lining in the tunnel is set to 20°C. Taking different high geothermal environments (40°C, 60°C and 80°C) and different lining materials (ordinary lining concrete, thermal conductivity 1.8W / (m·K); SAP geopolymer concrete of the present invention, thermal conductivity 0.8W / (m·K)) as variables, the cooling effect inside the tunnel under the same time is studied. The initial support of the surrounding rock adopts the method of shotcrete. The temperature changes inside the tunnel at different times (24h, 48h, 72h and 96h) using two lining concretes (ordinary lining concrete and SAP geopolymer concrete of the present invention, with a lining thickness of 0.5m) under different high geothermal environments (40°C, 60°C and 80°C) are compared. A monitoring line is set to calculate the temperature values ​​at various times and positions inside the tunnel. The tunnel clearance monitoring line is as follows: Figure 4 The blue area is shown by the red line.

[0043] The temperature change results of the tunnel clearance monitoring line are as follows: Figures 5 to 7 As shown in the figure, the ordinary lining represents ordinary lining concrete, the new lining represents the SAP geopolymer concrete of the present invention, the ordinate value is the temperature value, the abscissa value is the distance value of a monitoring line extending from the center point of the tunnel to the lining boundary, point A represents the center of the tunnel, point B represents the position 2.5m away from the center of the tunnel, and point C represents the position 4.5m away from the center of the tunnel (at the inner wall of the tunnel lining). Figure 4 shown. Figures 5 to 7 The blue straight line represents ordinary concrete lining; the red dotted line represents the SAP geopolymer concrete lining of the present invention. Different marks on the line represent different moments, as shown in the figure.

[0044] By comparison Figures 5 to 7From the temperature changes of the monitoring lines at the same time (with the same mark) under different working conditions, it can be observed that: as time goes by, the temperature inside the tunnel gradually increases. However, whether it is 40°C, 60°C, or 80°C, the temperature change curve of ordinary lining concrete is always above the curve of the SAP geopolymer concrete of the present invention. This shows that in the same period of time, the temperature rise rate of the environment in the tunnel is faster when ordinary lining concrete is used than when the developed SAP geopolymer concrete is used, which is not good for the construction environment. The SAP geopolymer concrete developed by the present invention has a low thermal conductivity, and compared with ordinary concrete, it takes longer for the tunnel clearance to reach the same temperature. In other words, at the same time, SAP geopolymer concrete has a good cooling effect on the inside of the tunnel.

[0045] At the same time, it can be obtained from the similar change trend that the factors affecting the tunnel clearance in the high ground temperature environment are consistent: from the center of the tunnel to the inner boundary of the lining (from left to right along the red line), the degree of influence gradually increases and the temperature gradually increases. The SAP geopolymer concrete material of the present invention has well weakened this influence as a whole.

[0046] As the lining of the initial support, SAP geopolymer concrete has a low thermal conductivity and is effective in reducing the tunnel clearance temperature under 40°C, 60°C and 80°C working conditions, but the effects are different. The higher the high ground temperature environment, the more significant the reduction in the internal temperature of the tunnel, and the longer the heating time, the better the cooling effect.

[0047] The average temperature of each point after excavation is shown in Tables 5~7. The cooling effect is expressed by the degree of temperature change at the three positions A, B and C in the tunnel.

[0048]

[0049]

[0050]

[0051] The temperature at each position increases with time, and it can be seen from Tables 5 to 7 that: (1) The temperature values ​​at each point under the SAP geopolymer concrete lining are lower than those under the ordinary lining concrete; (2) At the same time (96h) at the center of the tunnel: at 40℃, the temperature value of ordinary lining concrete is 26~27℃, and the temperature value of SAP geopolymer concrete is about 23~24℃, and the average cooling effect is improved by 10.5%; at 60℃, the temperature value of ordinary lining concrete is 33~34℃, and the temperature value of SAP geopolymer concrete lining is 27~28℃, and the average cooling effect is improved by 17.4%; at 80℃, the temperature value of ordinary lining concrete is 41~42℃, and the temperature of SAP geopolymer lining is 32~33℃, and the average cooling effect is improved by 22.2%; (3) At 2.5 m from the center of the tunnel, at the same time (96 h): at 40 °C, the temperature under ordinary lining concrete was 28-29 °C, and the temperature under SAP geopolymer lining was 25-26 °C, with an average cooling effect of 10.5%; at 60 °C, the temperature under ordinary lining concrete was 37-38 °C, and the temperature under SAP geopolymer concrete lining was 31-32 °C, with an average cooling effect of 16.4%; at 80 °C, the temperature under ordinary lining concrete was 47-48 °C, and the temperature under SAP geopolymer concrete lining was 37-38 °C, with an average cooling effect of 20.3%; (4) At the same time (96 h) in the tunnel lining, at 40 °C, the temperature of the ordinary lining concrete was 32-33 °C, while the temperature of the SAP geopolymer concrete was about 29-30 °C, with an average cooling effect of 9.6%; at 60 °C, the temperature of the ordinary lining concrete was 45-46 °C, while the temperature of the SAP geopolymer concrete lining was 39-40 °C, with an average cooling effect of 13.3%; at 80 °C, the temperature of the ordinary lining concrete was 57-58 °C, while the temperature of the SAP geopolymer concrete lining was 48-49 °C, with an average cooling effect of 15.5%.

[0052] In summary, the average cooling effect at each location is shown in Table 8.

[0053]

[0054] It can be seen from Table 8 that at the same location, as the high ground temperature increases, the average cooling effect gradually increases, indicating that SAP geopolymer concrete has a better high temperature insulation effect. At the same temperature, the closer to the center of the tunnel, the better the cooling effect. SAP geopolymer concrete can effectively slow down the heat transfer of the surrounding rock, making the internal environment of the tunnel change more smoothly, which provides better protection for construction safety.

Claims

1. A SAP geopolymer shotcrete, characterized in that: The raw materials are prepared by the following mass proportions: 100 parts of cementitious material, 13-16 parts of alkali activator, 135-150 parts of river sand, 165-185 parts of gravel, 32-41 parts of water and appropriate amount of SAP; In terms of mass percentage, the amount of SAP is 0.2-0.3% of the cementitious material; the cementitious material is composed of slag and fly ash in a mass ratio of (0.24-0.26):

1.

2. The SAP geopolymer shotcrete according to claim 1, characterized in that: The slag is S95 grade slag.

3. The SAP geopolymer shotcrete according to claim 1, characterized in that: The fly ash is Class I fly ash.

4. The SAP geopolymer shotcrete according to claim 1, characterized in that: The particle size of the SAP is 300-500 μm.

5. The SAP geopolymer shotcrete according to claim 1, characterized in that: The alkaline activator is compounded from water glass and NaOH, and the modulus of the alkaline activator is 1.1-1.

3.

6. The SAP geopolymer shotcrete according to claim 1, characterized in that: The modulus of the river sand is 2.5~2.

9.

7. The SAP geopolymer shotcrete according to claim 1, characterized in that: The stone is natural stone with continuous grading of 5-12 mm.

8. The SAP geopolymer shotcrete according to claim 7, characterized in that: The composition of the 5-12 mm continuously graded natural stone is as follows: 35-45% of 5-8 mm small-size stone, 35-45% of 8-10 mm medium-size stone, and 10-30% of 10-12 mm large-size stone, based on the total mass of the stone.

9. The SAP geopolymer shotcrete according to claim 1, characterized in that: The preparation process is: (1) Preparation of alkaline activator: Calculate and weigh the required water glass and NaOH according to the modulus of water glass and the modulus of the alkaline activator. Pour the weighed NaOH into the water glass and stir immediately. After stirring, seal the mixture and place it at room temperature for 6 to 8 hours before use. (2) Weigh various raw materials in proportion. First, place river sand and gravel in a concrete mixer and dry mix them. Then pour slag, fly ash and SAP into the concrete mixer and dry mix them. Then pour the alkali activator into the concrete mixer and stir until the material becomes gelled. Then pour in a portion of water and stir evenly. Then pour in the remaining water and stir evenly again to obtain SAP geopolymer shotcrete.

10. Use of the SAP geopolymer shotcrete as claimed in any one of claims 1 to 9 in the primary lining of a high geothermal tunnel.

Citation Information

Cited By

  • High-performance sprayed concrete for high-ground-temperature tunnel and construction application method of high-performance sprayed concrete

    CN120903869A

  • High-performance sprayed concrete for high-rock-temperature tunnel and construction application method of high-performance sprayed concrete

    CN121021184A

  • Low-carbon high-impermeability sprayed concrete

    CN121202491A